Evaluation of dietary coffee Coffee canephora husk supplementation on the growth, blood chemicals, and antioxidative activity of red Nile tilapia Oreochromis sp. - Azmi Afriansyah; Mia Setiawati; Muhammad Agus Suprayudi; Ichsan Achmad Fauzi (Jurnal Akuakultur Indonesia)
Coffee by-products can be used as a feed additive for red Nile tilapia. This study aimed to evaluate the utilization of different dietary coffee husk supplementation dosages on the growth and antioxidative activity of red Nile tilapia (Oreochromis sp.). This study was designed following the completely randomized design experimental method, containing five dietary supplementation treatments, namely P0 (control, 0%), P1 (1%), P2 (2%), P3 (3%), and P4 (4%). Fish were reared for 8 weeks and fed three times a day. Parameters observed contained growth performance and antioxidative activity. The results showed that dietary coffee husk powder supplementation treatments provide higher growth than control treatment. Based on blood chemicals, coffee husk-supplemented diets could enhance the HDL content and reduce cholesterol, triglycerides, and LDL (P<0.05). Superoxide dismutase enzyme was also found higher in coffee husk supplemented diets than in control diet (P<0.05). The MDA level decreased on the coffee husk-supplemented diet treatment and was lower than the control treatment (P<0.05). Dietary supplementation of coffee husk could positively affect liver performance, based on hepatosomatic index and glycogen level. This study concludes that 4% coffee husk in the diet is considered the best treatment to improve the growth and antioxidation level of red Nile tilapia.